Levetiracetam in the prophylactic treatment of episodic migraine: A prospective open label study. (October 2022) - Evers, Stefan; Frese, Achim; Summ, Oliver; Husstedt, Ingo W; Marziniak, Martin
Background: The prophylactic treatment of migraine includes anticonvulsant drugs such as valproic acid and topiramate. However, these substances are often poorly tolerated by migraine patients. So far levetiracetam has hardly been studied as an episodic migraine prophylactic agent in adults. Objective: To perform a prospective pilot study for the evaluation of the efficacy and tolerability of levetiracetam in the prophylactic treatment of episodic migraine. Methods: Fifty patients with episodic migraine were enrolled in this prospective, open label study. After a baseline period of four weeks, patients received 1, 000 mg (starting dose 500 mg) bid levetiracetam for 12 weeks. Migraine frequency and accompanying symptoms were recorded in a headache diary. The primary endpoint was the comparison of attack frequency during the baseline with attack frequency during the last four weeks of treatment (treatment period 3). Results: In the Intent-To-Treat analysis, 46% of the patients had a migraine reduction of more than 50% in the third period as compared to the baseline period. The mean number of migraine attacks decreased from 5.2 +/− 2.1 (baseline) to 3.4 +/− 2.7 (period 3). The most frequently reported side effects were somnolence, nausea, and weight gain; all were mild and transient. In a post-hoc comparison, responders to levetiracetam had significantly less migraine attacks at baseline and had significantly more often migraine with aura. Conclusion: The data suggest that levetiracetam has some potential in the prophylactic treatment of episodic migraine which seems, however, to be not superior to that of other anticonvulsant drugs. Levetiracetam was well tolerated and showed better efficacy in patients with migraine with aura and in less affected migraine patients. A larger placebo-controlled, double-blind study in adults seems justified on the basis of these data.